2021
DOI: 10.1080/00130095.2021.1874242
|View full text |Cite
|
Sign up to set email alerts
|

Pulling Effects in Immigrant Entrepreneurship: Does Gender Matter?

Abstract: We examine whether the existing stock of immigrant firms induces more new firms of the same nationality in the same sector and province. We carry out the analysis by using Italian administrative data on the population of individual firms observed over the time window 2002-2013. We find support for a strong attractiveness (pulling) effect, which significantly differs by gender, with female immigrant entrepreneurs showing a lower reactiveness to the existing stock of firms compared to their male counterparts. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The Italian context is characterized by a generally low rate, albeit at an increasing pace, of participation of women as entrepreneurs (Colombelli et al , 2020) as well as managers (Devicienti et al , 2019; Bruno et al , 2018), with substantial differences between geographical areas. Together with traditional and cultural differences, the preliminary evidence on macro-areas motivates an extension of our analysis to regional differences and features, to give a deeper understanding of our main findings.…”
Section: Resultsmentioning
confidence: 99%
“…The Italian context is characterized by a generally low rate, albeit at an increasing pace, of participation of women as entrepreneurs (Colombelli et al , 2020) as well as managers (Devicienti et al , 2019; Bruno et al , 2018), with substantial differences between geographical areas. Together with traditional and cultural differences, the preliminary evidence on macro-areas motivates an extension of our analysis to regional differences and features, to give a deeper understanding of our main findings.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary, [68] using Mexico to examine the impact of remittances on inequality conclude that remittances lower inequality. Other empirical studies have found remittance to reduce income inequality [69][70][71][72][73][74] while others finds no significant effects [75,76].…”
Section: Remittance and Income Inequalitymentioning
confidence: 99%
“…Existing empirical evidence suggests that age, education, wealth and family structure are important. Moreover, migrant men and women may have different propensities to become entrepreneurs (see, for example, Colombelli et al, 2021). Immigrant-owned businesses are also more concentrated in certain sectors, such as construction, trade or professional services (Fairlie and Lofstom, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing literature shows that gender plays a relevant role in shaping the probability of being self-employed (see e.g. Colombelli et al, 2021, andOggero et al, 2020). Table 3 reports estimated marginal effects by gender and suggests two interesting implications.…”
Section: Gendermentioning
confidence: 99%